Safe Food, Dangerous Lands? Traditional Foods and Indigenous Peoples in Canada - Robin, Tabitha; Burnett, Kristin; Parker, Barbara; Skinner, Kelly (Frontiers in Communication, 2021)
There is a deep and troubling history on Turtle Island of settler authorities asserting control over traditional foods, market-based and other introduced foods for Indigenous peoples. Efforts to control Indigenous diets and bodies have resulted in direct impacts to the physical, emotional, mental and spiritual well-being of Indigenous peoples. Food insecurity is not only a symptom of settler colonialism, but part of its very architecture. The bricks and mortar of this architecture are seen through the rules and regulations that exist around the sharing and selling of traditional or land-based foods. Risk discourses concerning traditional foods work to the advantage of the settler state, overlooking the essential connections between land and food for Indigenous peoples. This article explores the ways in which the Canadian settler state undermined and continues to undermine Indigenous food sovereignty through the imposition of food safety rules and regulations across federal, provincial, and territorial jurisdictions.